Authentication of β-casein milk phenotypes using FTIR spectroscopy. (June 2022) - Daniloski, Davor; McCarthy, Noel A.; O'Callaghan, Tom F.; Vasiljevic, Todor
Abstract: The ability to accurately and cost-effectively distinguish between different genetic protein variants in milk is of pivotal significance to the dairy industry as the natural proteoforms of caseins affect the composition and functionality of dairy products. Recently, β-casein proteoforms have received increased consumer attention in regards to A1 and A2 milk families. Fourier transform infrared (FTIR) spectroscopy coupled with multivariate analysis was used to discriminate milk samples from 114 Holstein-Friesian cows possessing different β-casein genetic variants. Principal component and partial least squares-discriminant analyses were used to characterise and distinguish A1 and A2 β-casein genetic families based on spectral data. Milk containing A2 β-casein had higher proportions of random coil and β-sheet conformations than milk containing A1 β-casein and the lowest amount of α-helical and β-turn structures, due to additional proline. This may provide a feature to distinguish between these phenotypes using FTIR spectroscopy in association with chemometric analyses.